2016
DOI: 10.3855/jidc.6862
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial susceptibility patterns of Propionibacterium acnes isolated from patients with acne vulgaris

Abstract: Introduction: Propionibacterium acnes has been implicated in the development of acne vulgaris. Rampant use of topical and systemic antibiotics for acne vulgaris has led to resistance due to selective pressure. This study aimed to determine antibiotic resistance of P. acnes. Methodology: A total of 102 samples were collected from acne lesions and cultured onto sheep's blood agar and brain-heart infusion agar supplemented with 5 g/L glucose and 2 mg/L furazolidone) (BHIg) under aerobic and anaerobic conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
1
19
0
4
Order By: Relevance
“…was relatively high in both groups (more than 54%) and did not differ significantly in term of CFU load. The literature reports various levels of resistance among C. acnes strains: from 6.1% to 7.6% of EryR strains to 98% of EryR strains, with various intermediate levels . Nevertheless, it is worth mentioning that in most of these studies, (i) sampling was performed on the skin (with swabs) and did not always take into account the pilosebaceous gland containing C. acnes ; and (ii) one Cutibacterium isolate (the main) per patient was isolated by culture on nonselective agar (without antibiotics), then its sensibility to antibiotics was analysed.…”
Section: Discussionmentioning
confidence: 99%
“…was relatively high in both groups (more than 54%) and did not differ significantly in term of CFU load. The literature reports various levels of resistance among C. acnes strains: from 6.1% to 7.6% of EryR strains to 98% of EryR strains, with various intermediate levels . Nevertheless, it is worth mentioning that in most of these studies, (i) sampling was performed on the skin (with swabs) and did not always take into account the pilosebaceous gland containing C. acnes ; and (ii) one Cutibacterium isolate (the main) per patient was isolated by culture on nonselective agar (without antibiotics), then its sensibility to antibiotics was analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the reported resistance rates have varied according to regions and have shown dynamic changes. The numbers of variables are enormous, as shown in Table 1 15–49 . The evaluation and comparison should consider the chronologic development, study setting (hospital based, general practice or in the general population), demographic backgrounds (age and gender), bacteria examined ( P. acnes, S. epidermidis or S. aureus ), sampling sites (face/forehead/cheeks/nostrils, back), sampling nische (lesional or non‐lesional, skin surface or follicular canal), types and severity of acne, pretreatment including types, doses, administration form, and duration of antibiotics, methods of bacterial isolation, and the detection and definition of antibiotic resistance.…”
Section: The Historical Changes Of Antibiotic Resistance In Acnementioning
confidence: 99%
“…In 2013, a sampling of 98 patients showed that more than half of them were colonized with strains that are resistant to clindamycin and erythromycin [10]. In contrast, a study by Biswal et al showed that only 10% of isolates were resistant to clindamycin [11]. In a recent prospective study, Zhu et al demonstrated that many strains were sensitive to tetracyclines but higher resistant patterns were seen in patients who received topical or systemic antimicrobial therapy [12].…”
Section: Discussionmentioning
confidence: 99%